2018
DOI: 10.1029/2018wr023055
|View full text |Cite
|
Sign up to set email alerts
|

Unsurprising Surprises: The Frequency of Record‐breaking and Overthreshold Hydrological Extremes Under Spatial and Temporal Dependence

Abstract: Record‐breaking (RB) events are the highest or lowest values assumed by a given variable, such as temperature and precipitation, since the beginning of the observation period. Research in hydroclimatic fluctuations and their link with this kind of extreme events recently renewed the interest in RB events. However, empirical analyses of RB events usually rely on statistical techniques based on too restrictive hypotheses such as independent and identically distributed (i/id) random variables or nongeneral numeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 100 publications
0
16
0
Order By: Relevance
“…On any given year t , the number of stations with a flood occurrence corresponds to the number of successes among n t trials, with varying success probabilities (),,π1πnt. The corresponding distribution is known as the Poisson‐binomial distribution (Hong, ; Serinaldi & Kilsby, ). The red area in Figure shows the corresponding 95% probability interval, which closely follows the observed frequency of occurrence.…”
Section: Resultsmentioning
confidence: 99%
“…On any given year t , the number of stations with a flood occurrence corresponds to the number of successes among n t trials, with varying success probabilities (),,π1πnt. The corresponding distribution is known as the Poisson‐binomial distribution (Hong, ; Serinaldi & Kilsby, ). The red area in Figure shows the corresponding 95% probability interval, which closely follows the observed frequency of occurrence.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, spatial correlations were not explicitly accounted for in the method. The occurrence of more floods than expected within any given space‐time window may be less surprising when spatial correlations are considered (Serinaldi & Kilsby, 2018). Analyses of the flood discharge records (not shown here) suggest that there is some spatial correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the long-term behavior of the hydrological cycle and its driving forces provide the context to understand that correlations between hydrological samples not only occur, but they also can persist for a long time (see O'Connell et al, 2016, for a recent review). While Leadbetter (1974Leadbetter ( , 1983) demonstrated that distributions based on dependent events (with limited long-term persistence at extreme levels) share the same asymptotic properties of distributions based on independent trials, there is evidence that correlation has strong influence on the exact statistical properties of extreme values and it slows down the already slow rate of convergence (e.g., Bogachev & Bunde, 2012;Eichner et al, 2011;Serinaldi & Kilsby, 2016;Volpi et al, 2015). In essence, correlation inflates the variability of the expected values and the width of confidence intervals due to information redundancy, and a typical effect is reflected in the tendency of hydrological extremes to cluster in space and time (e.g., Serinaldi & Kilsby, 2018, and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Then, correlation structures and variability of hydrological processes might easily be underestimated, further compromising the attempt to draw conclusions about trends spanning the period of records (see Serinaldi et al, , for detailed discussion). In other words, the lately growing body of publications examining “nonstationarity” in hydrological extremes (see Salas et al, , and references therein) may likely reflect time dependence of such extremes within a stationary setting, as observed patterns are usually compatible with stationary correlated random processes (Koutsoyiannis & Montanari, ; Luke et al, ; Serinaldi & Kilsby, ).…”
Section: Introductionmentioning
confidence: 99%